Peritoneal Dialysis-Related Peritonitis With : A Case Report - Tushar Bajaj MD; Nader Ismail DO; Anuja Trivedi MD; Menaka Sarav MD (SAGE Publishing, 2023)
We demonstrate the first reported case of peritoneal dialysis (PD)-related peritonitis with Acinetobacter pittii . Although previous reports have reported the uncommon similar infection in the larger Acinetobacter calcoaceticus - baumannii complex group of organisms, none have particularly focused on A pittii . Furthermore, we present a case of a young man with end-stage renal disease on PD who had a severe infection with A pittii . Although the organism was sensitive to ceftazidime, and despite a 4-week extended course of intraperitoneal antibiotics, the patient had a worsening infection leading to the removal of the PD catheter. Furthermore, the case illustrates the importance of proper sterile technique and hand hygiene, as this may have been the nidus of infection for this case.